PENGARUH KUALITAS PRODUK DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN MOTOR HONDA BEAT PADA KONSUMEN HONDA JATIWARINGIN - Morganda Silaban; Sunartiyo (Jurnal Ekonomi dan Industri, 2020)
This study aims to determine the effect of product quality and price on purchasing decisions of Honda Beat motorcycles simultaneously and partially on Honda Jatiwaringin consumers. In addition this study also aims to determine whether there are differences in consumer perceptions on the independent variable of the study when viewed from demographic factors (age, gender, income). Purposive Sampling is a sampling technique in this study. Research data were obtained by distributing research questionnaires about product quality, prices and purchasing decisions to 100 respondents. Multiple regression analysis, F test, T test is a data analysis technique in this study using the IBM SPSS Statistics 23 application. The results of the study show that (1) Product quality and price have a simultaneous effect on purchasing decisions, (2) Product quality and price influence partially on purchasing decisions, (3) there were no differences in consumer perceptions on each of the independent variables of the study when viewed from demographic factors.